Biology and therapeutic implications of VEGF‐A splice isoforms and single‐nucleotide polymorphisms in colorectal cancer. Issue 10 (2nd February 2017) - Canavese, Miriam; Ngo, Doan T.M.; Maddern, Guy J.; Hardingham, Jennifer E.; Price, Timothy J.; Hauben, Ehud
Abstract : Tumor growth, dissemination and metastasis are dependent on angiogenesis. The predominant vascular endothelial growth factor (VEGF) isoform that plays a major role in angiogenesis is VEGF‐A. Indeed, VEGF‐A is implicated in promoting angiogenesis of numerous solid malignancies, including colorectal cancer (CRC). A large body of preclinical and clinical evidence indicates that the expression of specific VEGF‐A isoforms represents a predominant pro‐angiogenic factor, which is associated with formation of metastases and poor prognosis in CRC patients. Different isoforms of human VEGF‐A have been identified, all of which arise from alternative splicing of the primary transcript of a single gene. Notably, it has been recently demonstrated that expression of type 3 isoform pattern is significantly correlated with venous involvement in CRC as well as in progression to metastatic colorectal cancer (mCRC), although it remains unclear what proportion of CRC tumors express these isoforms. This review highlights the importance of investigating the genetic and the epigenetic variations in VEGF‐A pathways in CRC, the functions of different VEGF‐A isoforms and their potential application as prognostic markers and/or therapeutic targets. Better understanding of the mechanisms controlling angiogenesis in liver metastases is necessary to address the limitations of current anti‐angiogenic therapies.